Corn and Soybean Yield as Affected by Cover Crop and Phosphorus Fertilizer Management - Megan A. Bourns; Elaheh Khosh Manzar; Nathan O. Nelson; Kraig L. Roozeboom; Gerard J. Kluitenberg; Ganga M. Hettiarachchi; Elizabeth A Yeager; Peter J. Tomlinson; DeAnn R. Presley (Kansas Agricultural Experiment Station Research Reports, 2023)
Phosphorus (P) fertilizer additions are often required to meet crop nutrient demands, but over-fertilization can have economic consequences, as well as environmental consequences from agricultural P loss. Therefore, we require management strategies that balance crop P demand and the need to minimize environmental P loss. The objective of this study was to investigate the effect of cover crop addition and P fertilizer management strategy [build and maintain (BM), sufficiency (SF), and a zero-P control (CN)] on crop yield of a no-till, corn-soybean system for 2020, 2021, and 2022 crop years for a site near Manhattan, KS. The addition of a cover crop decreased corn yield in 2021, and soybean yield in 2022, compared to the no cover treatment. In all three years of the study, both BM and SF management increased crop yield compared to the control, and BM and SF yields were similar, overall.
Keywords: yield; cover crops; fertilizer